A proposal for energy efficient design: an IFC based design decision system and its application - TÜRKYILMAZ, EMRAH (WIT Press, 2014)
Today, a large part of the total energy consumed in buildings is used to provide adequate indoor air quality and indoor lighting. The dirt and noise of urban environments encourage keeping buildings closed tight, with a resultant reliance on mechanical systems. Despite tightening the building envelope to decrease energy consumption, the building itself becomes more dependent on mechanical systems and monitors to assure adequate heat, ventilation and air-conditioning. The need, amount and the timing of energy efficient air conditioning are the subjects of studies, which include how to provide efficient air conditioning to control indoor air quality. Within this context, the aim of the research is to develop a design decision system to provide sufficient and consistent knowledge on air-conditioning for the design process. Today, there are only a few systems serving the same aim with a very limited capacity. These systems are not designed to be either cost-effective or industrial applicable. Air-conditioning and air circulation analysis of spaces are made by CFD (Computer Fluid Dynamics) software. In order to use air-conditioning and air circulation analysis in design process efficiently, CFD analysis software and BIM (Building Information Modelling) software should work together. Three steps are followed to develop the proposed system. First, what the results of air circulation analysis used by architects is composed of. Second, an interface is designed to define air circulation analysis in BIM software. Third, additional properties set to Industry Foundation Classes (IFCs) standard to keep analysis data on BIM model is prepared. A computer laboratory and a conference room are chosen to test the developed system. The evaluation of preliminary test results are shown that the developed system produces easily understandable graphic analysis for architects. While using the proposed system, air conditioning is no longer a very general characteristic of a design process but it is a real design feature forming the overall design process.
Keywords: energy efficient design; BIM; IFC; CFD